Associations Between Dynamic Strength Index and Jumping, Sprinting and Change of Direction Performance in Highly Trained Basketball Players - Jernej Pleša; Filip Ujaković; Chris Bishop; Nejc Šarabon; Žiga Kozinc (Applied Sciences)
The aim of this study was to investigate associations and differences between dynamic strength index (DSI) and multi-directional jumping, linear and curvilinear sprinting, and change of direction (CoD). Highly trained basketball players (n = 44) performed a 20 m linear sprint, 20 m 3-point line (curvilinear) sprint, countermovement jump (CMJ), drop jump (DJ), bilateral horizontal jump, unilateral horizontal jump, lateral jump, basketball-specific lateral jump and isometric mid-thigh pull (IMTP). The results showed weak to moderate associations between IMTP performance and horizontal jump, lateral jump and curvilinear sprint (r = −0.33–0.41; p < 0.05). No correlations were found between CMJ peak force and performance variables, while weak correlations were observed between DSI and unilateral horizontal jump (r = −0.36; p < 0.05), lateral jumps, linear sprint and CoD deficit (r = −0.37, −0.38; p < 0.05), showing that lower magnitude of DSI is associated with better performance in those tests. Additional analysis revealed that the low DSI subgroup had the highest IMTP peak force, while the high DSI subgroup had the highest CMJ peak force. The low DSI group showed better performance in vertical, horizontal and lateral jumps, while no significant differences were observed in DJ and curvilinear sprint performance compared to other groups. The findings indicate that athletes with lower DSI values exhibit superior physical performance, suggesting that a strength-oriented training approach may be beneficial for basketball players. Due to the ballistic nature of basketball, more maximal strength training is required to optimize the DSI ratio in basketball players. Additional studies are needed to determine the precise benchmarks for navigating training based on DSI values.